Case report: Whole exome sequencing reveals a novel splicing variant of ANKRD17 gene in a Chinese male juvenile with developmental delay and transient tic disorder - Chen, Jing; Yang, Shuo; Wang, He; Wang, Hongjing; Xiao, Yuanyuan; Liu, Shanling (Frontiers in Genetics, 2024)
Background The Ankyrin Repeat Domain Containing Protein 17 (ANKRD17, OMIM:615929) gene is a protein-coding gene associated with diseases such as Chopra-Amiel-Gordon Syndrome and Non-Specific Syndromic Intellectual Disability. The protein encoded by ANKRD17 gene belongs to the ankyrin repeat-containing protein family, which is one of the most widely existing protein domains that exclusively mediate protein-protein interactions. To date, the research and reports on the ANKRD17 gene are limited. Case presentation Trio whole exome sequencing (Trio-WES) was conducted on the proband and his unaffected parents to elucidate the genetic etiology in the proband, who was clinically diagnosed with developmental delay and other phenotypes. Subsequently, Sanger sequencing was employed for validation of the identified candidate variant. Furthermore, RNA analysis was utilized to ascertain the impact of the variant on splicing. The WES revealed a novel heterozygous ANKRD17 splicing variant (c.7248 + 1G>A) in the proband, but not detected in his unaffected parents. And the presence of the splicing variant of the ANKRD17 gene was valided by the Sanger sequencing subsequently. And the RNA analysis confirmed that the novel variant was predicted to result in loss of donor splice site, and the analysis at mRNA level confirmed that it leads to exon 32 skipping (r.7100_7278del179) and causes premature termination of translation to the protein (p.D2357fs), therefore is classified as pathogenic. Conclusion Our study reported a novel splicing variant in ANKRD17 gene, which may be associated with partial eating, frequent urination, and tic syndrome. This finding expands both the phenotypic and genotypic spectrum of ANKRD17 gene. Although there is currently no curative therapy available for ANKRD17 gene variants, a definitive diagnosis of its genetic etiology is significant for genetic counseling and family planning purposes. Furthermore, this is the first reported case of the ANKRD17 gene in China.